Fixers agency, translation, and the early global history of literature - Stahuljak, Zrinka (Chicago The University of Chicago Press, 2024)
"In this book, Zrinka Stahuljak issues a challenge to scholars working in medieval studies to account for the history of translation, and to experts in translation studies to read the work of medievalists. Focusing on the term "fixer," she unpacks modern uses of the words "interpreter" and "translator" and restores them to their premodern origins: as an active agent who performed a wide range of tasks, as insider informant, local guide, broker of knowledge, and transmitter of art. For Stahuljak, the fixer was a multifunctional intermediary, not a mere translator or interpreter (in the restricted modern sense), but an enabler, facilitator, and mediator, the engine driving the exchange of multiple linguistic, social, cultural, and topographic forms of knowledge. She proposes a paradigmatic shift for both medieval literary history and for the history of translation to confront and interrogate each other in their core disciplinary practices, which promote national, political, and colonial agendas masked as neutrality. Surveying a variety of texts from 1250 to 1500, including crusade treatises and travel writings, accounts of pilgrims and spies, chronicles and romances in both prose and verse, and traversing an impressive range of languages, including Latin, Middle French, German, Italian, and Spanish, Stahuljak asks both medievalists and translation studies scholars to reconsider their assumptions and methods as a way to reconstruct a premodern, precolonial, inclusive world literature"--
Fixers: Toward an alternative history of translation and literature -- Historical realities: strategy, loyalty, and gift ; The politics of translation: foreign language acquisition, conversion, and colonization (thirteenth- and fourteenth-century crusade treatises) ; The economy of translation: missionaries to the Mongol Empire, pilgrims to the Holy Land, and the gift of languages (thirteenth to fifteenth centuries) -- Disciplinary realities: authorship, genre, and literary history ; The ethics of translation: loyalty, commensuration, and literary forms in the fourteenth century (Machaut, Froissart, Mézières) ; Fixer literature: (pseudo)translation and manuscript illumination (the fifteenth-century court of Burgundy) ; The hermeneutics of translation: authorship and genre (the fifteenth-century court of Burgundy) -- Conclusion Fixers: early world literature in the age of the global